RELIABILITY AND VALIDITY OF THE LATVIAN VERSION OF THE EMOTION REGULATION SKILLS QUESTIONNAIRE - Kristiņa-Everte, Iluta; Paiča, Inese; Mārtinsone, Kristīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The aim of this study was to carry out the adaption of the Latvian version of the Emotion Regulation Skills Questionnaire (ERSQ-27)(SEK-27, Berking & Znoj, 2008) for adults witch evaluates nine dimensions of emotion regulation skills. The questionnaire was completed by 376 adults (82% women and 18% men), aged 18 – 69 years (M = 31.2, SD = 12.99). The calculations for the adapted questionnaire were made for the Cronbach’s alpha, test-retest reliability and determination of the convergent and factorial validity. The five-factor solution proposed by the exploratory factor analysis (EFA) was tested and compared with the theoretically postulated nine-factor solution using confirmatory factor analysis (CFA). The nine-factor model results in the Latvian version questionnaire explain 72% of varienace, but five-factors – 59.76%. The results for EFA and CFA were both higher in the nine-factor model. The internal consistency coefficients (Cronbach’s alpha) of the scales varied from 0.64 to 0.82, test-retest correlations ranged between 0.82 – 0.94. Similar results of the factor analysis were found in other research studies. Findings from this study showed significant evidence for the reliability and validity of the ERSQ-27 and it would be advisable to continue using it in scientific research.